ANALISIS PENINGKATKAN KUALITAS KOMPETENSI APARATUR PEMERINTAH DAN PELAYANAN PUBLIK DALAM MEWUJUDKAN GOOD GOVERNANCE DI JAWA TENGAH - Hilda Salma Jundia; Aris Eddy Sarwono; Dewi Saptantinah Puji Astuti (Politeknik Negeri Ambon, 2023)
The purpose of this research is to create a government in Indonesia that is oriented towards the competence of government apparatus and public services in order to realize good governance, and has not yet been implemented in all regions in Indonesia. Because the lower the level of governance, the more often they have direct contact with the community in demonstrating competence and the services they provide. So it is necessary to enact the principles of good governance as the ideals of the nation. Improving the competence of government apparatus should adhere to a paradigm oriented towards the interests of the community in providing services to the wider community, preparing all tools to meet this paradigm systematically (from input-process-output-results/impact), so that quality services are realized (which may be tangible). , reliable, responsive, safe, and full of empathy in its implementation). The concept of good governance is an ideal form of governance formulated by experts for the practice of establishing good relations between the state, society and markets. The type of research used is descriptive quantitative method including the official BPS website, and previous journals. The results of this study show that the government continues to strive to improve the competence of government officials so that people can get maximum service from competent government officials. The quality of public services in Indonesia has been included in the green category, which means high quality of service compliance to the government. In the service process, the government always strives for the public to more easily access all the facilities that have been provided on a digital basis.